Does Isoniazid Preventive Therapy Provide Better Treatment Outcomes in HIV-Infected Individuals in Northern Ethiopia? A Retrospective Cohort Study - Tesfay Mehari Atey; Helen Bitew; Solomon Weldegebreal Asgedom; Asrat Endrias; Derbew Fikadu Berhe (AIDS Research and Treatment)
Objectives. Early antiretroviral therapy (ART), isoniazid preventive therapy (IPT), and isoniazid-rifapentine (3HP) are effective strategies for preventing tuberculosis (TB) among people living with HIV (PLHIV). The study aimed to determine the effect of IPT on the TB incidence, follow-up CD4+ T cells, and all-cause mortality rate. Participants. Eligible patients on ART (n = 1, 863) were categorized into one-to-two ratios of exposed groups to IPT (n = 621) and nonexposed groups to IPT (n = 1, 242). Exposed groups entered the cohort at their first prescription of IPT, and unexposed groups entered into the study at the first prescription of ART and then followed until the occurrence of the outcome or date of administrative censoring (June 30, 2017). The outcome endpoints were TB incidence, follow-up CD4+ T cells, and all-cause mortality rate. Results. The follow-up CD4+ T cells for the exposed and nonexposed groups were 405.74 and 366.95 cells/mm (World Health Organization (WHO), 2017), respectively, a statistically significant finding (t1861 = −3.770, p<0.0001; Cohen’s d = 0.186). Nine percent of the exposed patients (620 incidence of TB per 100,000 person-years (PYs)) and 21.9% of the nonexposed patients (3160 incidence of TB per 100,000 PYs) developed TB. Mortality rate (per 100,000 PYs) was 440 for the exposed and 1490 for the unexposed patients. Statistically significant determinants of the all-cause mortality were unscheduled follow-up (AHR = 1.601; 95% CI: 1.154–2.222) and unable to work properly (AHR = 2.324; 95% CI: 1.643–3.288). Conclusion. This study demonstrates the effect of IPT in reducing incidence of TB and all-cause mortality rate and improving follow-up CD4+ T cells. Promoting IPT use can help to achieve the TB eradicating national agenda in Ethiopia.